Researches on the Constitutive Models of Artificial Frozen Silt in Underground Engineering. (17th June 2014) - Yang, Yugui; Gao, Feng; Cheng, Hongmei; Lai, Yuanming; Zhang, Xiangxiang
Abstract : The researches on the mechanical characteristic and constitutive models of frozen soil have important meanings in structural design of deep frozen soil wall. In the present study, the triaxial compression and creep tests have been carried out, and the mechanical characteristic of frozen silt is obtained. The experiment results show that the deformation characteristic of frozen silt is related to confining pressure under conventional triaxial compression condition. The frozen silt presents strain softening in shear process; with increase of confining pressure, the strain softening characteristic gradually decreases. The creep curves of frozen silt present the decaying and the stable creep stages under low stress level; however, under high stress level, once the strain increases to a critical value, the creep strain velocity gradually increases and the specimen quickly happens to destroy. To reproduce the deformation behavior, the disturbed state elastoplastic and new creep constitutive models of frozen silt are developed. The comparisons between experimental results and calculated results from constitutive models show that the proposed constitutive models could describe the conventional triaxial compression and creep deformation behaviors of frozen silt.